PENGARUH SERTIFIKASI TANAH TERHADAP NILAI ASET DAN KESEJAHTERAAN EKONOMI MASYARAKAT: STUDI LITERATUR EKONOMI - Loso Judijanto (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyse the effect of land certification on asset value and economic welfare through an economic literature review. Land certification as an instrument for legalising land ownership provides legal certainty that increases the economic value of land and opens up access to various formal financial services for the community. Literature review indicates that secure land ownership through certification can stimulate investment, reduce agrarian conflicts, and promote local economic growth and social stability. However, the success of land certification in improving community economic welfare is highly dependent on the implementation context, supporting policies, and the inclusiveness of access to certificates. This study provides recommendations for integrating land certification programmes with supporting policies to maximise sustainable social and economic benefits. Thus, land certification not only increases asset value but also becomes the foundation for community economic empowerment.